PELATIHAN DETEKSI DAN PERBAIKAN KESALAHAN BERBAHASA MELALUI KELAS BENGKEL BAHASA BAGI SISWA SMA NEGERI TAMPAKSIRING - Dewa Ayu Widiasri; Nyoman Astawan; I Nyoman Sadwika (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
The use of standard Indonesian among senior high school students continues to face challenges, particularly in spelling, diction, effective sentence construction, and paragraph development. The influence of informal language varieties, social media language, and code-mixing practices often affects students’ academic writing. This community service program aimed to strengthen students’ standard Indonesian proficiency through a Language Workshop Class at SMA Negeri Tampaksiring. The program employed a participatory training approach with four stages: pre-test, workshop implementation, module development, and post-test evaluation. The workshop was conducted in four sessions, covering (1) introduction to standard Indonesian and common errors, (2) identification of language errors in students’ own texts, (3) editing and revision practice, and (4) final text production and presentation. Data were collected through tests, observations, questionnaires, and analysis of students’ revised writing products. The results showed a significant improvement in students’ language proficiency. The average pre-test score of 61.8 increased to 83.4 in the post-test, with a gain of 21.6 points. Improvements were most evident in spelling and effective sentence construction, followed by diction and paragraph coherence. In addition, the program produced a Bengkel Bahasa module as a sustainable learning output for the school. These findings indicate that the Language Workshop Class is effective in improving students’ standard Indonesian proficiency and can serve as a practical strategy for strengthening academic literacy in secondary education.